Experience with fetal monitoring in a university teaching hospital. - Koh, K. S. (1975)
Fetal monitoring during labour may be expected to decrease perinatal losses and the number of infants born with brain damage. In a prospective study of intrapartum fetal monitoring in selected high-risk pregnancies in a Winnipeg hospital the monitoring rate was 26.5% and the cesarean section rate in the monitored group was 22.0%. The fetal outcome in the monitored group was better than in the unmonitored group. The establishment of a fetal intensive care unit is believed to be strongly desirable in improving fetal surveillance during labour. Fetal monitors should be stationed in the delivery room as well as in the first-stage room.